2021
DOI: 10.1177/17427150211010600
|View full text |Cite
|
Sign up to set email alerts
|

Leadership lessons untold: A new history of Robert McNamara’s World Bank

Abstract: Leadership education can be reductionist and facile. Recent scholarship in management and organizational history has reexamined many of the most established business school concepts and literatures, rethinking the ‘lessons’ taught from – among others – Taylor, Maslow and the Human Relations School. This study similarly uses historical methods (oral historical and archival) to analyse the career of Robert S. McNamara, a major figure often portrayed simplistically in leadership literature. McNamara is often char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…School strict administration may influence a subconscious encouragement to the teacher in order to meet the expected criteria lined by the upper administrative person. However, in management field, this may sound unrelated with common knowledge, as excessive burden might bring bad influence to the employee (in this case, teachers) (Heath & McCann, 2021;Milligan et al, 2022;Milosevic et al, 2020) On the other hand, public schools might rely more on traditional lecture-based approaches, potentially impacting students' ability to apply theoretical knowledge to practical scenarios tested (Elfaki et al, 2019), especially in the biology test. Our observation and note from teachers' response revealed that due to the teaching experience, many express that their main achievement is to earn the certification or work experience as the basic requirement of public service registration.…”
Section: Factor Influencing Students Performancementioning
confidence: 99%
“…School strict administration may influence a subconscious encouragement to the teacher in order to meet the expected criteria lined by the upper administrative person. However, in management field, this may sound unrelated with common knowledge, as excessive burden might bring bad influence to the employee (in this case, teachers) (Heath & McCann, 2021;Milligan et al, 2022;Milosevic et al, 2020) On the other hand, public schools might rely more on traditional lecture-based approaches, potentially impacting students' ability to apply theoretical knowledge to practical scenarios tested (Elfaki et al, 2019), especially in the biology test. Our observation and note from teachers' response revealed that due to the teaching experience, many express that their main achievement is to earn the certification or work experience as the basic requirement of public service registration.…”
Section: Factor Influencing Students Performancementioning
confidence: 99%
“…A multidimensional look at process management allowed Bitkowska (2019, pp. [130][131][132][133][134][135][136][137][138][139] to distinguish the following areas of IPM: -dimension: strategic fit, -dimension: corporate governance, -dimension: technologies and tools, -dimension: structure and culture, -dimension: human resources.…”
Section: Focus On the Process Vs Social Aspects Of Developmentmentioning
confidence: 99%
“…The discussion presented in this chapter is a continuation of various aspects of organizational leadership analysis, which is a complex issue dependent on many factors (Heath and McCann, 2021), the third one tackling formal issuesthe purposeful and rational impact of the organization on shaping leadership relationships and talent management practices. This chapter, in accordance with the character of the book, focuses specifically on the coexistence of formal solutions in the field of talent management and the development of leadership qualities and skills in the context of important aspects of business competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, over the years, Leadership has been under the radar of social scientists. For instance, an enormous amount of Literature is available on leadership which is studied under the lens of different theoretical foundations (Asif et al, 2020;Heath & McCann, 2021;Lee et al, 2020;Witzel, 2019). The earlier belief for studying leadership was to identify the physical, intellectual, and behavioral characteristics of successful leaders and provide them the opportunity to lead others (Deichmann & Stam, 2015;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%